A shared responsibility for Northern Ireland : why the EU and the UK should work together to find flexible solutions after Brexit - Ondarza, Nicolai von (2021)
Zusammenfassung: Even after the Brexit treaties have come into effect, the conflict over how to deal with Northern Ireland is still straining relations between the European Union and the United Kingdom. From London’s perspective, the Northern Ireland Protocol leads to unacceptable economic, political, and social disruptions, which is why it is calling for a fundamental renegotiation. The EU, for its part, is accusing the British government of failing to fully comply with its obligations under the protocol. The recent extension of some of the protocol’s grace periods has mitigated the conflict somewhat, but it only works to postpone the difficult decisions into the future. A serious political dispute continues to simmer in the background, with negative implications for the still difficult UK-European relationship. But simply insisting on London’s legal obligations is insufficient – the EU should show flexibility in implementation but demand that London unequivocally accepts the protocol